The compliance of zakat income among Felda prodata’s staff / Nadiah Abu Nawar - Abu Nawar, Nadiah (Faculty of Business and Management, 2014)
Zakat is the third pillars of Islam which should be fulfilled by any Muslim in the whole world. Muslims should acquire their wealth with their own spending and needs for others, nowadays most of Muslim in Malaysia not really understands about how importance zakat compliance is especially zakat on income that because of lack of knowledge in paying zakat from their income. As we can see, most of zakat institution not really exposes the important of payment zakat through their income. Therefore, this study is conducted to determine the important of compliance on zakat on income among Felda Prodata’s staff. Those interm of factors that make payers comply are: Income level, knowledge, attitude of zakat payer. In this study, 110 questionnaires were distributed to Felda Prodata Kuala Lumpur which has been distributed the questionnaire to all departments such as Corporate Department, Finance Department, Human Resources Department, Marketing Department, System Department, K.Development Department, and Procurement Department but 100 quetionnaire has been used in this research. The finding of this study was obtained where the Pearson Correlation result confirmed relationships between the income level and compliance of zakat on income. Compliance of zakat on income was found to have the highest influence on knowledge (β = .898) followed by attitude of zakat payer (β = .891), and only income is get moderate relationship with compliance of zakat on income (β = .469) From the finding, the researcher The researcher recommends to government to amend a system that the zakat automatically deducted from payer’s income is either income from private company, semi-government or government itself. Besides, all zakat institutions need to spread the knowledge widely. Such as give a talk to all company especially Muslim company about the important of compliance of zakat on income. last but not list, all entertainment industry especially television station or radio station should give more exposure or advertisement about the important of zakat.